Music composer’s online artistic responses and online lessons during and post-lockdown - Salleh, Marzelan; Mohamed Razali, Camellia Siti Maya (Faculty Of Human Ecology, Universiti Putra Malaysia, 2021)
The Covid-19 pandemic has brought upon the world new normality onto various aspects of our lives. An area of the arts that has been profoundly affected, and not necessarily in an undesirable way is, music. Music has always been a part of our lives either directly or indirectly. However, the lockdowns implemented all over the world due to Covid-19 pandemic has forced or voluntarily made music makers and composers create their art in purely online environments. With an increased number of audience presences online during the pandemic, composers are innovatively using media extensively to create, and the artistic results have been more intimate, emotional, and personal with the inclusion of a more direct communication with audiences. Composers and music makers are writing music either in seclusion or apart, while producing unnecessarily solo pieces but also all kinds of mixed ensembles. Music is then recorded and brought upon together through technology, and sometimes encouraging collective creativity. At the same time, social isolations have brought upon an increase in online digital connections with concerts, ensembles, and musical being live streamed online. Alternative and conventional creative spaces of composers are created either intentionally or unintentionally indoor or outdoor of private spaces – balcony, bedroom, living room, or the house garden. During the pandemic, themes of musical content include communicating self-emotions and self-expressions. This paper shall discuss into artistic responses of composers and give an insight into the ways music is created and communicated and how we, as humans, listen and watch music during and after the pandemic concern. The creative and performing spaces and themes are also discussed in this article. This article also looks upon the composers’ role as educators and how the lockdown situations have changed their composition lessons.